Identificación de la entomofauna en el transecto n° 6 parte b cantón Pujilí, provincia Cotopaxi, 2016 - Gallo Cevallos, Sylvia Susana (2017)
The present research aims to observe the effect of deforestation on the composition of entomofauna (micro fauna), in Transect No. 6 Part B, located in Laureles, La Esperanza-Pujilí. For the study the total area (1 hectare) was divided in transects and is located in the coordinates: Length 1°0'32.21'' S, Latitud 79°7'44.68'' W, Altitude 671 meters above sea level. The main objective of the project is to determine the diversity and abundance that exists in transect No 6, characterized by pasture with predominance of honey grass (Paspalum dilatatum), with the appropriate trapping, insect were collected, which were classified and identified at the entomology laboratory through the use of dichotomous keys, later conservation techniques were applied. A total of 2589 insects were identified, 35 families were identified, highlighting five dominant families. Formicidae family predominates with 63.90% in the studied transect. The estimated Shannon index in the 2589 insects collected, equals to 0.172055 of abundance, according to the analysis it was deduced that there is no significant difference in relation to the diversity of each of the 10 points, indicating that the transect has a homogeneous diversity.